Effects of Nd Content on Structure and Chemical Durability of Zirconolite–Barium Borosilicate Glass‐Ceramics. Issue 12 (10th August 2016) - Wu, Lang; Li, Huidong; Wang, Xin; Xiao, Jizong; Teng, Yuancheng; Li, Yuxiang
Abstract : The effects of Nd2 O3 content (0–12 wt %) on crystalline phases, microstructure, and chemical durability of barium borosilicate glass‐ceramics belonging to SiO2 –B2 O3 –Na2 O–BaO–CaO–TiO2 –ZrO2 –Nd2 O3 system were studied. The results show that the glass‐ceramics with 2–6 wt% of Nd2 O3 possess mainly zirconolite and titanite phases along with a small amount baddeleyite phase in the bulk. Calcium titanate appears when the Nd2 O3 content increases to 8 wt%, and the amount of quadrate calcium titanate crystals increases with further increasing content of Nd2 O3 . For the glass‐ceramics with 6 wt% Nd2 O3 (Nd‐6), Nd elements homogeneously distribute in zirconolite, titanite, and residual glass phases. There is a strong enrichment of Nd in calcium titanate crystals for the sample with 10 wt% Nd2 O3 . The viscosity of Nd‐6 glass is about 49 dPa·s at 1150°C. Moreover, Nd‐6 glass‐ceramics show the lower normalized leaching rates of B (LRB ), Ca (LRC a ), and Nd (LRN d ) when compared to that of the sample with 8 wt% Nd2 O3 . After 42 days, LRB, LRC a, and LRN d of the Nd‐6 glass‐ceramics are about 6.8 × 10 −3, 1.6 × 10 −3, and 4.4 × 10 −6 g·m −2 ·d −1, respectively.